Analisis Kualitas Produk Dan Kemasan Pada Keputusan Pembelian Roti Aroma Dengan Minat Beli Sebagai Variabel Intervening - Nasution, Ibnu Fajar; Purba, Rakhmawati (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This study aims to determine the effect of product quality and packaging on purchasing decisions with purchase intention as an intervening variable for consumers at Aroma Bakery Jl. Thamrin Tebing Tinggi City. The research method used is a quantitative method using SPSS version 25.00. The data collected from the results of distributing questionnaires to consumers of Aroma Bakery Shops in Tebing Tinggi City were 96 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination (R2) analysis, hypothesis testing, namely T test and path analysis. The results of SPSS in this study are the product quality affects the buying interest, the packaging affects the buying interest, the product quality affects the purchasing decision, The packaging has effect no significan on purchasing decisions, the buying interest has effect no significan on purchasing decisions and path analysis shows buying interest cannot mediate the relationship between product quality and purchasing decisions, and buying interest can mediate the relationship of packaging to purchasing decisions.